2016
DOI: 10.3390/ma9100819
|View full text |Cite
|
Sign up to set email alerts
|

Using Noise and Fluctuations for In Situ Measurements of Nitrogen Diffusion Depth

Abstract: In manufacturing processes involving diffusion (of C, N, S, etc.), the evolution of the layer depth is of the utmost importance: the success of the entire process depends on this parameter. Currently, nitriding is typically either calibrated using a “post process” method or controlled via indirect measurements (H2, O2, H2O + CO2). In the absence of “in situ” monitoring, any variation in the process parameters (gas concentration, temperature, steel composition, distance between sensors and furnace chamber) can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Magnetic Barkhausen noise (MBN) is a promising non-destructive technique that could be potentially adapted for fast and reliable surface monitoring. An increasing number of studies can now be found in which MBN is investigated as a function stress state [ 1 , 2 , 3 , 4 ], dislocation density [ 5 , 6 ], carbides or nitrides size and distribution [ 7 , 8 ], presence of non-ferromagnetic phases [ 9 ], etc. However, this technique is most widely employed for monitoring ground surfaces in real industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic Barkhausen noise (MBN) is a promising non-destructive technique that could be potentially adapted for fast and reliable surface monitoring. An increasing number of studies can now be found in which MBN is investigated as a function stress state [ 1 , 2 , 3 , 4 ], dislocation density [ 5 , 6 ], carbides or nitrides size and distribution [ 7 , 8 ], presence of non-ferromagnetic phases [ 9 ], etc. However, this technique is most widely employed for monitoring ground surfaces in real industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion couple (or diffusion multiple) technique is the most frequently used method to determine the interdiffusion coefficients and/or kinetic coefficients in the gas, liquid and solid states [ 16 , 17 , 18 , 19 ]. Literature surveys [ 20 , 21 , 22 , 23 ] indicate that most of the related publications available in the literature focus on the measurement of interdiffusivities in a single phase of the binary or ternary alloys with the aid of several reliable calculation methods (i.e., the Boltzmann-Matano method for binary systems [ 24 ], or the newly developed pragmatic numerical inverse method for binary, ternary and multicomponent systems [ 25 , 26 ]) together with the scientific error propagation method [ 27 , 28 ]. It should be noted that the so-called pragmatic numerical inverse method was augmented by fully considering the variations of interdiffusion flux into the calculation procedures [ 26 ].…”
Section: Introductionmentioning
confidence: 99%